In vitro selection of Neisseria gonorrhoeae unveils novel mutations associated with extended-spectrum cephalosporin resistance - Schörner, Marcos André; Mesa, Dany; Barazzetti, Fernando Hartmann; Martins, Jéssica Motta; Machado, Hanalydia de Melo; Grisard, Henrique Borges da Silva; Wachter, Julia Kinetz; Starick, Márick Rodrigues; Scheffer, Mara Cristina; Palmeiro, Jussara Kasuko; Bazzo, Maria Luiza (Frontiers in Cellular and Infection Microbiology, 2022)
The emergence of Neisseria gonorrhoeae strains resistant to extended-spectrum cephalosporins (ESCs) is a worldwide concern because this class of antibiotics represents the last empirical treatment option for gonorrhea. The abusive use of antimicrobials may be an essential factor for the emergence of ESC resistance in N. gonorrhoeae. Cephalosporin resistance mechanisms have not been fully clarified. In this study, we mapped mutations in the genome of N. gonorrhoeae isolates after resistance induction with cefixime and explored related metabolic pathways. Six clinical isolates with different antimicrobial susceptibility profiles and genotypes and two gonococcal reference strains (WHO F and WHO Y) were induced with increasing concentrations of cefixime. Antimicrobial susceptibility testing was performed against six antimicrobial agents before and after induction. Clinical isolates were whole-genome sequenced before and after induction, whereas reference strains were sequenced after induction only. Cefixime resistance induction was completed after 138 subcultures. Several metabolic pathways were affected by resistance induction. Five isolates showed SNPs in porin PBP2. The isolates M111 and M128 (ST1407 with mosaic penA-34.001) acquired one and four novel missense mutations in PBP2, respectively. These isolates exhibited the highest minimum inhibitory concentration (MIC) for cefixime among all clinical isolates. Mutations in genes contributing to ESC resistance and in other genes were also observed. Interestingly, M107 and M110 (ST338) showed no mutations in key determinants of ESC resistance despite having a 127-fold increase in the MIC of cefixime. These findings point to the existence of different mechanisms of acquisition of ESC resistance induced by cefixime exposure. Furthermore, the results reinforce the importance of the gonococcal antimicrobial resistance surveillance program in Brazil, given the changes in treatment protocols made in 2017 and the nationwide prevalence of sequence types that can develop resistance to ESC.